Protein cages, rings and tubes: useful components of future nanodevices? - Jonathan G Heddle (Dove Medical Press, 2008)
Jonathan G HeddleGlobal Edge Institute, Tokyo Institute of Technology, Nagatsuda, Midori-ku, Yokohama Kanagawa, JapanAbstract: There is a great deal of interest in the possibility that complex nanoscale devices can be designed and engineered. Such devices will lead to the development of new materials, electronics and smart drugs. Producing complex nanoscale devices, however will present many challenges and the components of such devices will require a number of special features. Devices will be engineered to incorporate desired functionalities but, because of the difficulties of controlling matter precisely at the nanoscale with current technology, the nanodevice components must self-assemble. In addition, nanocomponents that are to have wide applicability in various devices must have enough flexibility to integrate into a large number of potentially very different environments. These challenges are daunting and complex, and artificial nanodevices have not yet been constructed. However, the existence of nanomachines in nature in the form of proteins (eg, enzymes) suggests that they will be possible to produce. As the material from which nature’s nanomachines are made, proteins seem ideal to form the basis of engineered components of such nanodevices. Initially, engineering projects may focus on building blocks such as rings, cages and tubes, examples of which exist in nature and may act as a useful start point for modification and further development. This review focuses on the recent research and possible future development of such protein building blocks.Keywords: bionanotechnology, protein engineering, nanomachine, building-blocks, synthetic biology